Reconstruction Model For Mitigating Business-To-Customer Fraud In Indonesia’s VAT Policy - Adiningsih, Triana Eva; Mustikasari, Elia (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2025)
Purpose: This research aims to examine the possibility of combining E-Barimt and blockchain technology with E-Filing. This examination hopes that if the implementation of E-Barimt can be adopted into the Indonesian system, then the government will have another option of increasing tax revenue rather than increasing the tariff of VAT. Method: This research employs a systematic literature review as its method. The literature used comprises Scopus-indexed journals and grey literature—the latter was utilised due to the limited information available on Scopus-indexed journals regarding the e-Barimt. Results: The implementation of E-Barimt in Mongolia yields more beneficial effects, and with some adjustments, the author argues that it can also be implemented in Indonesia. Implications: This research presents a model for integrating E-Barimt, E-Filing, and Blockchain technology. This model can be implemented by policymakers in Indonesia to mitigate potential fraud, thereby supporting the government's goal of increasing tax revenue. Novelty: E-Barimt has never been mentioned in a Scopus-indexed journal, so this is considered a new system that scholars have not discovered. Besides, the effectiveness can be adopted in Indonesia and solve the VAT’s loopholes.